Gompertz Fréchet Strength of a component between two stresses Reliability Estimation - Sarah Adnan; Nada Sabah Karam (Al-Qadisiyah Journal of Pure Science, 2021)
In this paper, the reliability of the stress-strength model is derived for probability P( <X< ) of a component strength X between two stresses ,  , when X and ,  are independent Gompertz Fréchet distribution with unknown and known shape parameters and common known scale parameters. Different methods used to estimate R and Gompertz Fréchet distribution parameters which are [Maximum Likelihood, Least square, Weighted Least square, Regression and Ranked set sampling methods], and the comparison between these estimations by simulation study based on mean square error criteria. The comparison confirms that the performance of the maximum likelihood estimator works better than the other estimators.